Farmers organizations and food availability in Senegal: An impact analysis using a spatial econometrics approach - K. Christophe Adjin; Christian H. C. A. Henning (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2019)
This paper investigates the empirical causal relationship between farmers organizations membership and food availability in Senegal. Using a unique country scale farm-level data of cereals farming households, and applying various econometrics estimations techniques that control for selection biases and spatial heterogeneity, the study found positive and significant association between organizations membership and farmers levels of cereals production. Findings are consistent across estimations methods. Being a member of an farmer organization increases cereals production by 19%. These results suggest once again the importance of farmers organizations in the fight against rural food insecurity. In addition, other factors such as the access to extension services, fertilizer subsidies and the rainfall appear to be significantly determining households food production. Furthermore, results also reveal the relevance of spatiality in the analysis of agricultural sector in developing countries.
Keywords: Q13; 330; farmers organizations; impact evaluation; spatial heterogeneity